Effect of Health Education Videos on Knowledge and Attitudes of Teenage Pregnancy in Timor Leste - Moniz, Maria de Fatima; Astuti, Andari Wuri; Purwati, Yuni (Universitas Muhammadiyah Surakarta, 2026)
The high prevalence of adolescent pregnancy in Timor-Leste reflects vulnerabilities in adolescents’ reproductive health, particularly limited knowledge and unfavorable attitudes toward sexuality, which increase engagement in premarital sexual behavior and the risk of unintended pregnancy. However, empirical evidence explaining the role of reproductive health status in linking these outcomes, as well as the effectiveness of video-based reproductive health education in low-resource settings, remains limited. This study aimed to evaluate the effectiveness of video-based reproductive health education in improving knowledge and attitudes toward teenage pregnancy among female adolescents. A quasi-experimental one-group pretest–posttest design was conducted among 96 female students aged 17–18 years at ESGP de Suai, Covalima, Timor-Leste, selected through simple random sampling. The intervention consisted of a 15 minute reproductive health education video addressing adolescent pregnancy, related risks, and prevention strategies. Knowledge (20 items) and attitudes (10 items) were measured using a validated questionnaire (Cronbach’s α = 0.679 and 0.520, respectively). Effectiveness was defined as a statistically significant improvement in post-intervention knowledge and attitude scores. Data were analyzed using the Wilcoxon signed-rank test and the Mann–Whitney U test. Significant improvements were observed in knowledge (Z = −8.526; p < 0.001) and attitudes (Z = −8.532; p < 0.001) after the intervention. No significant difference was found between the magnitude of improvement in knowledge and attitudes (p = 0.850). Video based reproductive health education effectively improves adolescents’ knowledge and attitudes toward teenage pregnancy and represents a feasible intervention for adolescent reproductive health promotion in resource-limited settings.